EMPOWERING MSMES IN SUPPORTING THE TOURISM INDUSTRY BY FACILITATING MSMES FEATURES IN SMART TOURISM APPLICATIONS - Sularso Budilaksono; Euis Puspita Dewi; Fahrul Nurzaman; Ahmad Rosadi; Febrianty Febrianty (Darmabakti Cendekia: Journal of Community Service and Engagements, 2022)
Background: PT. Yoy International Management is a sharia-based hotel development and management company that formed in October 2020. It was born during the Covid-19 pandemic that hit almost all sectors of the tourism and hospitality industry in the world. PT. Yoy Management take a role in the recovery period and enable the tourism, hospitality and MSME sectors to support tourism by carrying out the sharia concept (trust, transparency, accountability). Objective: To empower MSMEs so that their products or services can be accessed in the Smart Tourism application. Methods: The method used to carry out learning in the form of sharing, focus group discussions and consultation with MSME actors and providing facilities for products and services in smart tourism applications. Sharing session approach as many as 6 activities for 2 months. MSME actors can enter products and services offered to tourists through the Sharia-based Smart Tourism Information System managed by PT. Yoy Management. The total number of MSMEs participating consists of 23 people, i.e. 13% tourism object managers; 21,7% restaurant managers; 17,4% car rental managers; 17,4% MSME managers; 21,7% hotel managers; and 8,7% tourists. Results: Based on questions about the product displayed on the Yoy application, the following answers were obtained: 65,2% very well; 30,4% good; and 4,4% less. Based on questions about tourist payments for service/product orders, the following answers were obtained: 43,5% very easy; 52,9% easy; and 4,3% difficult. Conclusion: The empowerment of MSMEs in the tourism industry is expected to increase MSME income and regional income.